Human microsatellite and minisatellite DNA polymorphisms - Weber, James (Henry Stewart Talks, 2007)
Microsatellites: nomenclature and definitions, Discovery, Typing methodology, Abundance and types, Applications, Mutation, Biological functions, Evolution, Minisatellites
Archived at 2020/08/13